Mechanics, models and methods in civil engineering - Maceri, Franco; Fremond, Michel (Lecture Notes in Applied and Computational Mechanics, 2012)
"Mechanics, Models and Methods in Civil Engineering" collects leading papers dealing with actual Civil Engineering problems. The approach is in the line of the Italian-French school and therefore deeply couples mechanics and mathematics creating new predictive theories, enhancing clarity in understanding, and improving effectiveness in applications. The authors of the contributions collected here belong to the Lagrange Laboratory, an European Research Network active since many years. This book will be of a major interest for the reader aware of modern Civil Engineering.